Effectiveness of out-of-home day care for disadvantaged families: randomised controlled trial - Toroyan, Tami (BMJ Publishing Group Ltd., 2003)
Objective To assess the effects of providing daycare facilities for young children on the health and welfare of disadvantaged families. Design Randomised controlled trial. Eligible children from the application list to a daycare facility were randomly allocated to receive a daycare place or not. Setting Early Years daycare centre in Borough of Hackney, London. Participants 120 mothers and 143 eligible children (aged between 6 months and 3.5 years). Intervention A place at the centre, which provided high quality day care. Control families used other child care that they secured for themselves. Main outcome measures Maternal paid employment, household income, child health and development. Results At 18 months' follow up, 67% of intervention group mothers and 60% of control group mothers were in paid employment (adjusted risk ratio 1.23 (95% confidence interval 0.99 to 1.52)), but were no more likely to have a weekly household income of above £200 (risk ratio 0.88 (0.70 to 1.09)). Intervention group children had more otitis media with effusion (risk ratio 1.74 (1.02 to 2.96)) and used more health services (1.58 (1.05 to 2.38)), but both estimates were imprecise. Conclusion The provision of child day care may have increased maternal employment, but it did not seem to increase household income. The results suggest that providing day care may be insufficient as a strategy to reduce poverty. The study shows how random allocation can be used to ration and evaluate interventions where demand exceeds supply.